2020
DOI: 10.1039/d0cp00741b
|View full text |Cite
|
Sign up to set email alerts
|

O–H vibrational motions promote sub-50 fs nonadiabatic dynamics in 3-hydroxypyran-4-one: interplay between internal conversion and ESIPT

Abstract: The OH out-of-plane bend vibration induces an extremely rapid S2 to S1 internal conversion in 3-hydroxypyran-4-one.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 83 publications
0
4
0
Order By: Relevance
“…Both investigations led to similar conclusions on a critical role of a conical intersection between bright S and dark S states, of respective * and n * character, which was interpreted as the reason for observation of two ESIPT rate constants for these molecules in the experiment. Anand et al applied the same methodology to study ESIPT also in similar 3-hydroxyflavone [ 150 ] and 3-hydroxypyran-4-one [ 151 ] systems, confirming the important role of the S state in their photorelaxation. Finally, recent thorough work by Cao et al provided theoretical insights on ESIPT-driven mechanism and quantum dynamics of thermally activated delayed fluorescence in triquinolonobenzene [ 152 ], in which singlet-state ultrafast proton transfer occurs within a dense manifold of low-lying triplet states.…”
Section: Nonadiabatic Molecular Dynamic Approachesmentioning
confidence: 97%
See 1 more Smart Citation
“…Both investigations led to similar conclusions on a critical role of a conical intersection between bright S and dark S states, of respective * and n * character, which was interpreted as the reason for observation of two ESIPT rate constants for these molecules in the experiment. Anand et al applied the same methodology to study ESIPT also in similar 3-hydroxyflavone [ 150 ] and 3-hydroxypyran-4-one [ 151 ] systems, confirming the important role of the S state in their photorelaxation. Finally, recent thorough work by Cao et al provided theoretical insights on ESIPT-driven mechanism and quantum dynamics of thermally activated delayed fluorescence in triquinolonobenzene [ 152 ], in which singlet-state ultrafast proton transfer occurs within a dense manifold of low-lying triplet states.…”
Section: Nonadiabatic Molecular Dynamic Approachesmentioning
confidence: 97%
“…Looking toward future developments that would further strengthen the field, support from machine learning techniques should definitely be considered a promising direction for the QD efficiency enhancement, with first results already emerging [ 153 , 154 ], so as to improve the performance of other dynamic approaches [ 155 ]. Moreover, linking solvent-dependent optical properties with nonadiabatic ESIPT dynamics within the fully quantum framework could also provide powerful new tool to the existing set [ 151 ], opening new-level possibilities, e.g., for describing the competition between intra- and intermolecular excited-state proton transfer reactions on equal footing.…”
Section: Summary and Future Outlookmentioning
confidence: 99%
“…Recently, Anand et al studied the dynamics of ESIPT reactions in 3-hydroxypyran-4-one, revealing that the O–H vibrational motion could promote sub-50 fs nonadiabatic dynamics. 31 Bisht et al studied the ESIPT reactions of salicylic acid (SA) monomer and dimer, and they found that the emission spectrum was dominated by progressions in the O–H stretch and in-plane distortion of the carboxylic group. 23 In this discussion, to elucidate the lack of ESIPT bands in o -aminoaldehyde derivatives, the N–H vibrational motion should be taken into account.…”
Section: Introductionmentioning
confidence: 99%
“…Dynamics methods on the other hand allow the explicit simulation of the proton transfer reaction. Full quantum dynamics methods such as Multi-Configuration Time-Dependent Hartree (MCTDH) [39][40][41][42][43][44] and semi-classical approaches such as Ab Initio Multiple Spawning (AIMS) 45,46 and surface hopping (with decoherence correction) [47][48][49][50][51][52][53] have been applied to investigate ESIPT. The Nuclear Electronic Orbital (NEO) method, which allows the full quantum treatment of a restricted set of nuclei (usually hydrogen), is a promising alternative in that context.…”
mentioning
confidence: 99%